Electroretinographic and Morphological Characterization of the Retina of Annexin A1 Knockout Mice - Rafael André da Silva; André Maurício Passos Liber; Luiz Philipe de Souza Ferreira; Francisco Manuel Moreno-Carmona; Diego Dias dos Santos; Monielle Sant’Ana; Marcelo Fernandes Costa; Dora Fix Ventura; Cristiane Damas Gil (Neuroglia, 2025)
Background/Objectives: The annexin A1 (AnxA1) protein has proven important in ocular disease homeostasis and holds great therapeutic promise. However, its role in the context of the healthy retina remains unknown. Therefore, this study used electroretinography (ERG) to investigate the role of endogenous AnxA1 in the retinal function of wild-type (WT) and AnxA1 knockout mice (AnxA1−/−). Methods: An extensive repertoire of full-field ERG was applied to AnxA1−/− and WT mice to examine retinal physiology. Morphometric analyses of the retina were conducted. Results: Our results revealed significant differences in the implicit time of a-wave and b-wave between the WT and AnxA1−/− groups under scotopic conditions. The negative and positive amplitude components of mesopic ON responses were higher in the AnxA1-/- group than in the WT group. In contrast, the implicit time of mesopic ON responses were significantly higher in the WT group than in the AnxA1-/- WT group. However, in photopic OFF responses, only the implicit time was significantly longer in the WT group than in the AnxA1−/− group. In the histomorphometric analysis, the retina of AnxA1−/− mice shows increased thickness. Conclusions: The absence of AnxA1 alters retinal morphology and physiology.